Training for awareness of one's own spirituality: A key factor in overcoming barriers to the provision of spiritual care to advanced cancer patients by doctors and nurses. Issue 3 (6th September 2018) - Bar-Sela, Gil; Schultz, Michael J.; Elshamy, Karima; Rassouli, Maryam; Ben-Arye, Eran; Doumit, Myrna; Gafer, Nahla; Albashayreh, Alaa; Ghrayeb, Ibtisam; Turker, Ibrahim; Ozalp, Gulcin; Kav, Sultan; et al.
Abstract: Objective: When patients feel spiritually supported by staff, we find increased use of hospice and reduced use of aggressive treatments at end of life, yet substantial barriers to staff spiritual care provision still exist. We aimed to study these barriers in a new cultural context and analyzed a new subgroup with "unrealized potential" for improved spiritual care provision: those who are positively inclined toward spiritual care yet do not themselves provide it. Method: We distributed the Religion and Spirituality in Cancer Care Study via the Middle East Cancer Consortium to physicians and nurses caring for advanced cancer patients. Survey items included how often spiritual care should be provided, how often respondents themselves provide it, and perceived barriers to spiritual care provision. Result: We had 770 respondents (40% physicians, 60% nurses) from 14 Middle Eastern countries. The results showed that 82% of respondents think staff should provide spiritual care at least occasionally, but 44% provide spiritual care less often than they think they should. In multivariable analysis of respondents who valued spiritual care yet did not themselves provide it to their most recent patients, predictors included low personal sense of being spiritual ( p < 0.001) and not having received training ( p = 0.02; only 22% received training). How "developed" a country is negatively predicted spiritual care provision ( p < 0.001). Self-perceived barriers were quite similar across cultures. Significance of results: Despite relatively high levels of spiritual care provision, we see a gap between desirability and actual provision. Seeing oneself as not spiritual or only slightly spiritual is a key factor demonstrably associated with not providing spiritual care. Efforts to increase spiritual care provision should target those in favor of spiritual care provision, promoting training that helps participants consider their own spirituality and the role that it plays in their personal and professional lives.